P-094 Non-adherence of Treatment in IBD Can Be Overestimated Depending of the Instrument. (March 2016) - Zaltman, Cyrla; Pinto, Márcia Ferreira; Costa, Marcia; de Oliveira, Christien
Abstract : Background: Non adherence to therapy is a common problem in the treatment of chronic diseases and may result in an increased morbidity. Multiple factors can be implicated: medications, sociodemographic and psychological aspects of the patient and until the doctor-patient relationship. Patient: The aim of this study is to evaluate the adherence to treatment in outpatients with inflammatory bowel disease (IBD) at a reference tertiary hospital. Methods: A descriptive cross-sectional pilot study involving 63 IBD outpatients (39 CD and 24 UC) was undertaken at a large teaching hospital from Rio de Janeiro (HUCFF-UFRJ). Institutional Review Board approval was obtained from the medical center. A semi-structured interview assessed demographic information (ethnicity, marital status, highest Educational Level, age) medical history (disease duration, drugs), disease knowledge, pertinent health behaviors, appointment keeping and medication adherence at the end of that clinic visit. Others factors that could influence adherence were assessed, such as satisfaction with care and complexity of the medical regimen (numbers of tablets, via). The Morisky test, a previously validated 4-item scale structured self-administered questionnaire was applied to assess medication adherence, permitting to evaluate if the detected behavior was intentional or not. It was considered as non adherence if any of the answers was "yes" to the item. Results: The mean age of respondents was 45 ± 12.2 years with 60.3% female, 63.5% having graduated from high school or higher. In 84.1% (53/63) of IBD patients, 79.5% CD (31/39) and 91.7% (22/24) UC, the drug non-adherence was predominant in 54.7% of IBD patients (29/63). The specific IBD drugs taken were: 5-ASA derivatives- 66.7% (42/63); thiopurines- 54%; (34/63); biological treatment 15.9% (10/63). Adherence was not significant different between these drug users. Factors such as age, education, presence of steady partner, diagnosis of CD or UC, disease and follow up duration, and number of ingested tablets monitoring and were not significantly associated with non-adherence ( P > 0.05). The disease knowledge assessed by the patient was very little and medium in 22% and 50.8% of included patients, respectively. Majority of patients (72%) were high satisfied with the doctor-patient relationship. It was detected a statistically significant association between the attendance to consultations and poor adherence ( P = 0.027). Conclusions: Most IBD patients were considered non-compliant with unintended behavior. Non-adherence was related to greater number of absences from medical appointments. The Morisky test is a validated and useful tool to assess adherence, is easy to apply, but of little flexibility and can overestimate the patient non adherence. Therefore other ways of evaluation should be used in an associated way to evaluate adherence.